The effect of organic loading rate on foam initiation during mesophilic anaerobic digestion of municipal wastewater sludge - Ganidi, Nafsika; Tyrrel, Sean F.; Cartmell, Elise (Elsevier Science B.V., Amsterdam., 2011)
The impact of increasing organic load on anaerobic digestion foaming was studied at both full and bench scale. Organic loadings of 1.25, 2.5 and 5 kg VS m(-3) were applied to bench-scale digesters. Foaming was monitored at a full scale digester operated in a comparable organic loading range over 15 months. The bench scale batch studies identified 2.5 kg VS m(-3) as a critical threshold for foam initiation while 5 kg VS m(-3) resulted in persistent foaming. Investigation of a full scale foaming event corroborated the laboratory observation that foaming may be initiated at a loading rate of 2.5 kg VS m(-3). Experimental findings on foam composition and differences in the quality characteristics between foaming and non-foaming sludges indicated that foam initiation derived from the combined effect of the liquid and gas phases inside a digester and that the solids/biomass ultimately stabilized foaming. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Foaming Anaerobic digestion Organic loading Sludge Filaments activated-sludge key process fermentation destruction stability behavior